Positive Impact of Similarity on Twice Single Seed Descent of Purification on Bambara Groundnut (Vigna subterranea L. Verdcourt) - Kuswanto Kuswanto; Prakit Somta (AGRIVITA, Journal of Agricultural Science, 2018)
The main problem of local line Bambara groundnut (Vigna subterranea L. Verdcourt) genotype improving is the low of purity. The research on genetic purification of Bambara groundnut had finished in twice single seed descent. The objective of this research was to find out the uniformity gain level within lines each other after single seed descent applied twice. This research was conducted in Agriculture Research Station, Universitas Brawijaya, from 2014 to 2016. There were 20 selected local lines evaluated twice with single seed descent method. On the first and second evaluation, it was applied on previous 19 local lines and 1 check genotype. Similarity coefficient was analyzed with cluster analysis of qualitative characters within lines. Variability within line was described on quantitative characters. The local lines had different response on single seed descent selection. These differences depended on genetic of qualitative characters. On the first single seed descent, it got similarity coefficient of 0.704-0.832. On the second one, it got similarity coefficient of 0.804-1.00. Increasing of similarity coefficient from 0.10-0.168 will improve purification of local lines 15.76-20.19 %. Two circles of single seed descent selection were capable to purify local lines. Variability of quantitative character depended on kind of character.